Isolation and Characterization of Curcumenotone, a Sesquiterpene from Curcuma aeruginosa Roxb as Antioxidant - Ririn Suharsanti; Subagus Wahyuono; Puji Astuti; Nunung Yuniarti (Indonesian Journal of Pharmacy, 2023)
Antioxidant compounds are necessary to block the initiation of oxidation chain reactions and inhibit the formation of ROS which are the cause of various diseases. Natural antioxidants can be isolated from various sources, one of them from Curcuma aeruginosa Roxb Rhizome. This study was aimed to isolate and identify antioxidant compounds from Curcuma aeruginosa Roxb rhizome. To isolate the active compound, the 2,2-diphenyl-1-picrylhidrazyl (DPPH) free radical scavenging activity guide was used. Initially the Curcuma aeruginosa Roxb rhizome powdered material macerated with ethanol 70% to give ethanol extract (EE). The EE was then fractionated gradually with increasing polarity solvents to give n-hexane (HF), ethyl acetate (EAF), ethanol (EF) and insoluble (IF) fractions. The EF was the active fraction, was fractionated  into 6 fractions (EE.a-f)  based on their TLC picture. Two compounds (EF.a1 and EF.a2)  were isolated from active fraction (EF.a) by preparative TLC. The EF.a2 appeared as white crystals demonstrates better activity as anti radical DPPH, having 96.24% purity (HPLC). EF.a2 appeared as a single peak in GC (Rt 12,78), and having molecular weight at m/z 234. There were 2 absorbtion peaks at 226 nm and 260 nm in Uv-Vis spectrophotometer and absorption bands at 3364, 3314, 2905 and 1653 cm-1 on the FT-IR spectrum. Based on spectroscopic data (1H-,13C-NMR) and comparison with reported data, the EF.a2 was identified as sesquiterpene, curcumenotone (C15H22O2). The curcumenotone was shown potent antioxidant in DPPH radical scavenging assay had an IC50 53.24±1.51 µg/mL, ABTS radical scavenging assay had an IC50 41.33±3.15 µg/mL, and FRAP assay had an IC50 37,82±2.02 µg/mL.